2012
DOI: 10.1152/ajpendo.00477.2011
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction pathways in FSH regulation of rat Sertoli cell proliferation

Abstract: The final number of Sertoli cells reached during the proliferative periods determines sperm production capacity in adulthood. It is well known that FSH is the major Sertoli cell mitogen; however, little is known about the signal transduction pathways that regulate the proliferation of Sertoli cells. The hypothesis of this investigation was that FSH regulates proliferation through a PI3K/Akt/mTORC1 pathway, and additionally, AMPK-dependent mechanisms counteract FSH proliferative effects. The present study was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 54 publications
5
91
0
2
Order By: Relevance
“…235 In contrast, FSH simulation of differentiating 15-to 20-day-old Sertoli cells increased cAMP levels but decreased ERK activity. 297 In other studies, FSH stimulation of 5-day-old Sertoli cells increased the levels of PIP3, a downstream target of PI3K signaling. Furthermore, inhibition of the pathway blocked Sertoli cell proliferation.…”
Section: Differential Fsh Signaling In Proliferating Versus Differentmentioning
confidence: 85%
See 1 more Smart Citation
“…235 In contrast, FSH simulation of differentiating 15-to 20-day-old Sertoli cells increased cAMP levels but decreased ERK activity. 297 In other studies, FSH stimulation of 5-day-old Sertoli cells increased the levels of PIP3, a downstream target of PI3K signaling. Furthermore, inhibition of the pathway blocked Sertoli cell proliferation.…”
Section: Differential Fsh Signaling In Proliferating Versus Differentmentioning
confidence: 85%
“…235 The FSH-mediated activation of ERK resulted in increased expression of cyclin D1 that promotes proliferation. 297 In the 8-day-old Sertoli cells, FSH stimulation also decreased activity of the AMPK that is associated with increased expression of the cell cycle inhibitors p19 INK4A , p21 Cip1 , and p27 Kip1 . 235,244,295,296 FSH also has been shown to activate the PI3K-AKT-mTORC1-p70S6K signal transduction pathway in Sertoli cells cultured from 8-day-old Sertoli cells.…”
Section: Differential Fsh Signaling In Proliferating Versus Differentmentioning
confidence: 95%
“…These cells express mTORC1 and mTORC2. mTORC1 is involved in FSH-mediated proliferation of in vitro cultured immature SCs, via the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) signal transduction pathway, which is known to promote cell proliferation [8]. mTORC1 also regulates the redox balance of in vitro cultured human SCs, and modulates the nutritional support that these cells provide to developing germ cells [9].…”
Section: Mtor Testis Physiology and Sertoli Cell (Sc) Functionmentioning
confidence: 99%
“…Additionally, previous study of Tanwar et al has suggested that aberrant AMPK-mTOR signaling causes disruption of SC polarity and spermatogenesis (Tanwar et al 2012). Well-coordinated AMPK-mTOR signaling is essential for SCs functions and survival (Riera et al 2012;Tanwar et al 2012). Thus, it is important to elucidate possible contribution of AMPK-mTOR signaling to NP-induced rat SC toxicity.…”
Section: Introductionmentioning
confidence: 97%